The Comparison of Learning Model Viewed from the Students Thinking Style - Mohamad Nur Fauzi; Budi Usodo; Sri Subanti (Intelektual Pustaka Media Utama, 2017)
The aim of the research was to determine the effect of learning models with scientific approach, characteristics thinking style, the interaction between learning model with scientific approach and characteristics thinking style toward mathematics achievement. This research was quasi-experimental research with factorial design 2 x 4. The population of research was all students of the seven graders of junior high school in Surakarta city in academic year 2016/2017. The sample of research consists of 190 students. The data in the research was two ways analysis of variance with unequal cells, with the 5% level of significance. The results of the research were as follow: (1) SFEs Learning model gave better mathematics achievement than direct instruction model: (2) Characteristics of Sequential concret (SK), sequential abstract (SA), random concret (AK), and random abstract (AA) thinking styles give the same effect on mathematics learning achievement; (3) In each learning model with SK, SA, AK, and AA thinking style characteristics have the same mathematics learning achievement. (4) In each of the SK, SA, AK, and AA thinking styles that are subject to the SFEs learning model and direct learning have the same mathematical learning achievement.